Performance Audit of Bio Medical Waste Management in West Bengal - CAG of India (CAG of India)
The Audit on Bio-Medical Waste Management covered a period of five years from April 2013 to March 2018 through examination of records of the Environment Department, WBPCB and H&FW Department. Besides, audit coverage was extended to Departments of Correctional Administration (CA), Home & Hill Affairs (H&HA) and Animal Resources Development. In addition, Common Bio-Medical Waste Treatment Facilities (CBMWTFs) were also covered in audit.
For the Period 2013-2018